Kasus Kateter Dialisis Peritoneal yang Terpuntir pada Seorang Anak - Cahyani Gita Ambarsari; Farhan Haidar Fazlur Rahman; Evita Karianni Bermanshah; Agustina Kadaristiana (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2020)
Objective: Mechanical complications of peritoneal dialysis (PD) may occur because of surgical complications when inserting a Tenckhoff catheter or non-surgical complications during chronic care of a PD catheter. We aim to highlight the latter by presenting a case report of twisted external catheter. Method: We report an 11-year-old Indonesian girl with end-stage renal disease on continuous ambulatory PD at Cipto Mangunkusumo Hospital who was hospitalized due to repeat peritonitis.Result: Upon examination, the external catheter seemed twisted without inflow, outflow, or ultrafiltration problems. Her exit score was 4 with gaping. Both abdominal X-ray and ultrasound showed that the catheter and its cuffs were properly placed. The patient frequently pulled and manipulated her PD catheter. Additionally, the catheter-site care procedure was frequently done by untrained caregivers and catheter fixation was also not performed. A retraining program for all involved caregivers was carried out. Peritonitis resolved after 14-day-treatment using intraperitoneal gentamicin. We determined that the twisted catheter and repeat peritonitis were due to a combination of mechanical trauma, poor chronic catheter-site care, and suboptimal PD catheter training. Conclusion: Maintaining compliance for chronic PD catheter exit-site care by well-trained caregivers and by patients themselves, as well as the external catheter fixation are important.